2018
DOI: 10.1186/s12958-018-0405-3
|View full text |Cite
|
Sign up to set email alerts
|

Mild ovarian stimulation with letrozole plus fixed dose human menopausal gonadotropin prior to IVF/ICSI for infertile non-obese women with polycystic ovarian syndrome being pre-treated with metformin: a pilot study

Abstract: BackgroundLetrozole is widely employed as ovulation induction agent in women with PCOS, but its use in mild stimulation (MS) protocols for IVF is limited. Aim of the present study was to evaluate the feasibility of a MS protocol with letrozole plus hMG in non-obese PCOS women undergoing IVF after a metformin pre-treatment.MethodsWe retrospectively evaluated the data of 125 non-obese PCOS undergoing MS with letrozole plus hMG, 150 IU as starting dose, (group 1, N = 80) compared to those undergoing a conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Additionally, it is also conceivable to use metformin and/or inositol to increase insulin sensitivity, and to induce ovulation with letrozole or a selective estrogen receptor modulator (SERM) [3]. Possibly, laparoscopic ovarian diathermy (LOD) or low dose FSH stimulation could be introduced in the case of SERM and/or letrozole resistance [31]. However, the abovementioned treatments promoting ovulation may lead to an increased risk of ovarian hyperstimulation syndrome (OHSS) in PCOS patients, in particular, those with high levels of anti-Müllerian hormone (AMH) [23, 30, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is also conceivable to use metformin and/or inositol to increase insulin sensitivity, and to induce ovulation with letrozole or a selective estrogen receptor modulator (SERM) [3]. Possibly, laparoscopic ovarian diathermy (LOD) or low dose FSH stimulation could be introduced in the case of SERM and/or letrozole resistance [31]. However, the abovementioned treatments promoting ovulation may lead to an increased risk of ovarian hyperstimulation syndrome (OHSS) in PCOS patients, in particular, those with high levels of anti-Müllerian hormone (AMH) [23, 30, 32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the abovementioned treatments promoting ovulation may lead to an increased risk of ovarian hyperstimulation syndrome (OHSS) in PCOS patients, in particular, those with high levels of anti-Müllerian hormone (AMH) [23, 30, 32]. It has been demonstrated that PCOS patients with high AMH levels are not only insensitive to the therapeutic effect of ovulation induction but also have a greater risk of OHSS [3134].…”
Section: Discussionmentioning
confidence: 99%
“…It has always been difficult to keep the balance between having a high pregnancy and minimizing OHSS. Patients with anovulation have high AMH and tend to have many follicles on stimulation, but they may also have a low response if stimulated with an inadequate dose of FSH [20][21][22]. In our study we could show that patients with high AMH, even some of them, do not have many oocytes nevertheless, had better pregnancy rate in the first cycle regardless of age.…”
Section: Discussionmentioning
confidence: 47%
“…Compared with standard GnRHagonist protocol, it related to lower OHSS rate, but had higher cycle cancellation rate. CLBR after repeated ovulation was not affected, and was mostly used for the decline of ovarian function [22][23][24]. In summary, the Prolonged GnRH-agonist protocol improves the CLBR of single oocyte collection in PCOS patients, and is the recommended scheme for IVF treatment in PCOS patients.…”
Section: Discussionmentioning
confidence: 97%